2010
DOI: 10.1186/1471-2164-11-548
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptomic profiles of zebrafish gills in response to zinc depletion

Abstract: BackgroundZinc deficiency is detrimental to organisms, highlighting its role as an essential micronutrient contributing to numerous biological processes. To investigate the underlying molecular events invoked by zinc depletion we performed a temporal analysis of transcriptome changes observed within the zebrafish gill. This tissue represents a model system for studying ion absorption across polarised epithelial cells as it provides a major pathway for fish to acquire zinc directly from water whilst sharing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…Kucukbay et al [45] showed that Zn supplementation decreased oxidative stress in rainbow trout. In zebrafish exposed to low (3 μg L −1 water and 26 mg kg −1 diet) or sufficient (16 μg L −1 water and 233 mg kg −1 diet) water and feed Zn concentrations, several general mechanisms in gill tissue were affected at deficiency, like down-regulation of developmental processes (26% of the genes in a 16K oligo nucleotide array), cell cycle, cell differentiation, gene regulation, butanoate metabolism, lysine degradation, protein tyrosin phosphatases, nucleobase, nucleoside and nucleotide metabolism, and cellular metabolic processes [46]. Genes among these groupings were associated to disorders like diabetes, bone tissue development and ionocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kucukbay et al [45] showed that Zn supplementation decreased oxidative stress in rainbow trout. In zebrafish exposed to low (3 μg L −1 water and 26 mg kg −1 diet) or sufficient (16 μg L −1 water and 233 mg kg −1 diet) water and feed Zn concentrations, several general mechanisms in gill tissue were affected at deficiency, like down-regulation of developmental processes (26% of the genes in a 16K oligo nucleotide array), cell cycle, cell differentiation, gene regulation, butanoate metabolism, lysine degradation, protein tyrosin phosphatases, nucleobase, nucleoside and nucleotide metabolism, and cellular metabolic processes [46]. Genes among these groupings were associated to disorders like diabetes, bone tissue development and ionocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher Zn absorption is found in low Zn diets [2]. Zheng et al [46] demonstrated the importance of including several time points for a better understanding of the homeostatic control mechanisms adjusting the fish body to changing Zn status.…”
Section: Discussionmentioning
confidence: 99%
“…HNF-4 is a transcription factor crucial for liver development, though it is expressed in some mammalian osmoregulatory tissues, such as kidney and intestine, for which its function remains to be determined (Grigo et al, 2008). The gene is also expressed in fish gill, where zinc deficiency induces transcription of HNF-4 and of genes enriched with HNF-4 binding elements (Zheng et al, 2010). Though a role in fish osmoregulation is novel, a homolog of HNF-4 appears crucial for coordinating osmoregulatory functions of excretory cells in nematode worms.…”
Section: Network Analysismentioning
confidence: 99%
“…Xenopus gene identifiers were transformed into their human orthologs to improve the richness of the output [72, 73]. In order to differentiate functional enrichment due to up- and down- regulated genes, the DAVID tool was used on any gene found up- or down-regulated at at least one time point from the genes found to be differentially transcribed at any time point.…”
Section: Methodsmentioning
confidence: 99%